Impacto do controle Volt/VAr em redes de distribuição a partir da exploração do potencial dos inversores de sistemas fotovoltaicos - Alves Filho, Pedro Genaro (2018)
The presence of Distributed Generation is a reality in the Brazilian electric sector, with the prospect that increasingly the participation of these sources contributes to the energy matrix of our country. Faced with this imminent growth, it is necessary to study the impacts caused by the injection of active power in distribution networks and how to mitigate these effects. The solution to the quest for greater system stability may be in managing the reactive power that some of the distributed generations are able to offer. This work presents a methodology to evaluate the impacts caused in the voltage, and how the fluctuation of this magnitude changes the behavior of the traditional voltage regulators in the system under study, due to the different operating conditions of the solar inverter when it operates in the fixed mode of factor of power unit and within the limits of the ABNT NBR 16149 Brazilian standard. It is also evaluated the use of a solar inverter capable of supporting the grid voltage through the management of reactive energy, a resource that is not yet consented to be used in Brazil's distribution networks. The developed methodology was validated in an IEEE 123 nodes test system, which represents a distribution feeder, with some proposed modifications. In view of the analysis of the system responses to the different operating modes of the inverter, it was possible to indicate the method that causes the least impact on the voltage profile of the evaluated system, and consequently indicate which causes the least number of voltage regulator maneuvers, taking as reference the scenario in which the feeder under study does not have distributed generations.